Perancangan Buku Ruang Terbuka Hijau Surabaya dengan Teknik Essay Photography guna Meningkatkan Kesadaran Lingkungan Hijau Masyarakat Kota Surabaya - Oktaviani, Ria; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Surabaya can be the learning object to study about how metropolitan city manage their area so that it has the existence of suitable green open space, concerning the fact that it has important role for environment. It is associated with the way the government of Surabaya City maintain and sought the existence of green open space in the middle of high land requirements as the Metropolitan City. Green open space is the most needed thing especially in urban area. The benefit of keeping the green environment especially in urban area is: direct benefit (within the meaning of quick and tangible) is shaping beauty and comfort (shady, fresh and cool) and gaining thing to be sold (woods, flowers and fruits), indirect benefit (long term and intangible), which is cleaning the air effectively, conserving and continuance of groundwater supply, preserving environmental function along with the content of flora and fauna exist (biological conservation and diversity). Keywords: Photography Essay Book, Green Open Space, Surabaya City, Enjoyable.